Optimal Strategy and Cost Effectiveness Analysis for Conservation of The Endangered Maleo: A Mathematical Approach - Darmawati; Nur, Wahyudin (Journal of Mathematics: Theory and Applications, 2025)
Maleo is a large megapod found on the island of Sulawesi and surrounding islands and is an endangered species due to illegal hunting and habitat conversion. In this article, we propose a mathematical model for Maleo conservation. The model that is constructed is expressed as a system of ordinary differential equations consisting of five equations. To study the optimal strategy, we use optimal control theory. In our model there are three control parameters related to guarding Maleo nests, monitoring Maleo habitats, and transferring Maleo eggs to captivity. To measure the impact and the consequences of each intervention scheme, we determine the percentage increase in the Maleo population and the average cost-effectiveness ratio. Our results show that the most effective intervention scheme to increase Maleo populations is a combination of guarding Maleo nests, monitoring Maleo habitats, and transferring Maleo eggs to captivity. Meanwhile, the intervention scheme that has the best cost-effectiveness is the intervention scheme which is a combination of guarding Maleo nests and monitoring Maleo habitats.